Konflik Undang-undang Perlindungan Anak dan Penegakan Disiplin Sekolah: Studi Kualitatif di SMA N 1 Kembang Jepara - Rosadi, Ima Dwi; Dewi Nur Cahyaningrum; Nela Veristika; Nurkolis (Media Manajemen Pendidikan, 2025)
The enforcement of discipline at school environment is important to create a condusive learning atmosphere. Howeverit sometimes faces child protection regulation poin 35 of 2014 about child’s protection. This study aims to examine the conflict appear between the implementation of disciplinary enforcement by the school and the legal limitations ruled in the child protection law, especially in SMA N 1 Kembang Jepara. The research method used a descriptive qualitative approach with data collection techniques and interviews, observations, and documentation studies. The result of the study showed there is dilemma faced by teachers and school stake holders in deciding strict action for students who break the rules for there is consideration of violating the children rights. This conflict appears because of lack of balanced understanding between legal protection for children and need for discipline in the education. The study recommends the need for special training for educators regarding legal limitations in enforcing discipline. As well as the importance of preparing national standart procedures (SOP)for discipline that are in line with statutory regulations. Effective communication could be done by the stake holders to minimize the different perception that triggers the emerged conflict.